La pedagogía del amor en el desarrollo de la motricidad fina en los niños de primer año de Educación Básica de la Unidad Educativa Hermano Miguel en el año lectivo 2020 - 2021. - Quishpe Olmos, Ana Lucía (2021)
This research work focused on the analysis of a methodological alternative for boys and girls, with the aim of strengthening fine motor skills through the pedagogy of love in First Year EGB children. Taking into consideration that fine motor skills is a fundamental aspect for the acquisition of future skills and knowledge and that during this educational level significant and innovative didactic activities should be promoted, for which, the fundamentals of love and affectivity are used, responding to the needs and interests of this vital stage. The problem focuses on the deficient level of knowledge and application of well-founded strategies where the infant's feelings and emotions prevail, where the affective and emotional part is positively involved for the integral child development. The methodological design applied is of a qualitative-quantitative approach, the research design is bibliographic and field, the modality is a feasible project, the research level is explanatory, the techniques used were observation, interview and survey. The main results obtained in the research lie in the contributions of this pedagogical alternative, as a guide for the development of a comprehensive, harmonious, holistic and creative educational process, thus favorably promoting fine motor skills in infants.